A mixed activity-based costing decision model for green airline fleet planning under the constraints of the European Union Emissions Trading Scheme - Tsai, Wen-Hsien; Lee, Kuen-Chang; Liu, Jau-Yang; Lin, Hsiu-Ling; Chou, Yu-Wei; Lin, Sin-Jin (Energy (Oxford), 2012)
This paper presents a mixed activity-based costing decision (MABCD) model for green airline fleet planning under the constraints of the European Union Emissions Trading Scheme (EU ETS), in which activity-based costing (ABC) model is incorporated with a modified product-mix decision model for total operating costs of individual flights under EU ETS constraints. A numerical example for comparing cost-effectiveness between the B747-400 airline and the A380 airline in one of the busiest route between Asia and Europe is demonstrated. It is shown that subject to different changes of revenue tone kilometers (RTK), the cost trends of carbon emissions and the changes in profits of different flight routes appear to be similar. Moreover, it is also shown that when the RTK are higher, a choice of a wider-bodied aircraft could lead to higher profits. Finally, it is shown that without the pre-assumptions of considering more complicated routes and financing methods, a self-purchased aircraft appears to contribute more profits. ► A pioneer study of incorporating CO2 emission costs into airline industries. ► CO2 emission costs are the key factor in selecting aircraft. ► The CO2 emissions cost trends and the changes of profits of flight routes appear to be similar. ► When the RTK are higher, a choice of a wider-bodied aircraft could lead to higher profits. ► Without financial issues, a self-purchase aircraft appears to contribute more profits.